The IITA farming systems program - Okigbo, B. (International Center for Research in Semi-Arid Tropics, 1974)
The International Institute of Tropical Agriculture (IITA) was established in 1967 on 1,000 hectares of land located at 3o 54'E longitude and 7o 30'N latitude, about 16 kiloneters north of Ibadan, the capital of the Western State of Nigeria. It is one of a network of international research institutes where priority is given to research, training and related activities aimed at quantitatively and qualitatively increasing food production in the developing countries of the world. These countries contine to experience shortages in available food supplies resulting from much higher rates of population growth as compared to the rates of increase in food production. Specifically, IITA's activities involve multidisciplinary, problem-oriented research in food crops production which, for effectiveness and rapid progress, is restricted to the major food crops of the humid tropics. The humid tropics is defined as the broad belt girdling the earth in the lower latitutes on both sides of the equator where precipitation exceeds evaporation for more than half the year and where normally the tropical rain forest constitutes the climax vegetation.